The design‐by‐treatment interaction model: a unifying framework for modelling loop inconsistency in network meta‐analysis. (20th November 2015) - Jackson, Dan; Boddington, Paul; White, Ian R.
Abstract : In this note, we clarify and prove the claim made Higgins et al . (2012 ) that the design‐by‐treatment interaction model contains all possible loop inconsistency models. This claim provides a strong argument for using the design‐by‐treatment interaction model to describe loop inconsistencies in network meta‐analysis. © 2015 The Authors. Research Synthesis Methods published by John Wiley & Sons, Ltd.